Clinical masks of T-cell lymphoma - O. V. Bulashova; E. V. Khazova; A. G. Pegov; D E. Maksimova; K. S. Chavro (Clinical Medicine (Russian Journal), 2026)
Some progress has been made in the study of the pathogenesis of peripheral T-cell lymphomas, which account for 10–15% of all non-Hodgkin’s lymphomas; however, diagnosis is diffi cult due to their rare occurrence and clinical and morphological diversity. Aim . to present data on the clinical course of peripheral T-cell lymphoma using a clinical example of patient Z. Material and methods. An analysis of literary sources was conducted and a case was presented demonstrating the difficulties in diagnosing non-Hodgkin’s T-cell lymphoma. Results and discussion. Patient Z., 56 years old, treated in a multidisciplinary hospital with the diagnosis of “Acute toxicoderma. Stevens–Johnson syndrome?” had been under the care of a dermatologist for dermatitis for 10 years. One month prior to hospitalization, he developed a skin rash covering his entire body with blistering, soreness, severe weakness, fever, difficulty swallowing, and joint pain. Despite treatment (prednisolone, meropenem, linezolid, fluconazole), the patient’s condition worsened, leading to multiple organ failure and death. Postmortem biopsy revealed peripheral T-cell lymphoma of unspecifi ed type and exacerbation of chronic dermatosis. Conclusions. This case confirms the aggressive course and poor prognosis of peripheral T-cell lymphoma, highlighting the unsatisfactory results of standard therapy. The disease’s onset, with hyperthermia, polyarthralgia, and skin changes, complicated the diagnosis of lymphoma, partly due to the lack of awareness and oncologic suspicion of oncohematological pathology among general practitioners and dermatologists. This case demonstrates the usefulness of immunohistochemical examination of the lesion biopsy, determining the extent of lymphoproliferative bone marrow lesions, and determining patient management strategies.